Advances in behavioural finance - Du Plessis, Jaco J (University of Pretoria, 2013)
A key question in behavioural finance is why prices in financial markets change. The field of behavioural finance evolved in an attempt to understand better and explain how cognitive errors and emotions influence investors' decision-making processes. Behavioural finance is the study of the psychological effects of market events on investors that affect finance decisions. It is not a new field of study, but more emphasis has been placed on this field of finance in the past two decades. Behavioural finance explores the irrational nature of investors' decisions. The primary objective of the research was to provide an understanding of the psychological impact of people on prices in financial markets. The secondary objectives are to provide a brief history of behavioural finance; to show that there are alternatives to the efficient markets theory; and to demonstrate the impact of popular models on prices. The report was compiled based on a literature study on the topic of behavioural finance. The purpose of the literature study was to provide sufficient information to meet the objectives of the study as set out above. The following sources were used: published articles; textbooks; and the Internet. The efficient market hypothesis and the CAPM are challenged by behavioural finance. Prices of speculative assets do not always reflect fundamental values. The perceptions of investors play an important role in the determination of prices. Hence, when there are market crashes on the equities markets, the contagion effect amongst investors should not be underestimated. It is shown in this report that portfolio insurance is an important contributing factor to the magnitude of any crash on equities markets. Dividends are an important determinant for the fundamental value of shares. This contrasts with the revenue model that is used to value new economy shares, such as Internet companies. It is also clear that investors expect to receive a dividend. In this report, various theories strongly suggest investors' preference for dividends. These include the self-control and prospect theories, regret-aversion and the clientele effect. Changes in dividends affect share prices. A decrease in the dividend of a company is a clear signal to investors that the share price is overvalued. Movements in share prices are therefore at least partially the result of changes in dividends. Investment strategies that can be followed by investors include the following: It may help to acquire closed-end fund shares at the listing of a new fund. The research shows that initially closed-end funds trade at a premium of up to ten per cent, but within 180 days, the premium evaporates and the fund starts to trade at a discount. The optimal strategy for sophisticated investors is a strategy that involves market timing with increased exposures to shares that have fallen, and decreased exposure to shares after they have risen in price. Individual investors should follow a buy-and-hold strategy, as opposed to a trading strategy, as the cost of trading is excessive. Arbitrageurs (professional investors) can earn higher than normal returns on markets that are excessively volatile. However, they need to be cautious, as they can also lose significant amounts of money when markets are volatile. Careful consideration should be given to what shares to trade, as the cost of trading is expensive, as much as six per cent. Furthermore, it is important to have stop-loss limits in place and to sell shares once they breach the lower limit that has been set. The notion that losing shares in a portfolio will somehow turn into winning shares is, in most cases, incorrect. Copyright 2003, University of Pretoria. All rights reserved. The copyright in this work vests in the University of Pretoria. No part of this work may be reproduced or transmitted in any form or by any means, without the prior written permission of the University of Pretoria. Please cite as follows: Du Plessis, JJ 2003, Advances in behavioural finance, MBA dissertation, University of Pretoria, Pretoria, viewed yymmdd < http://upetd.up.ac.za/thesis/available/etd-04202012-125738 / > F12/4/321/gm === Dissertation (MBA)--University of Pretoria, 2012. === Graduate School of Management === unrestricted